ChemInform Abstract: Nitration of Carbonic, Sulfuric and Oxalic Acid‐Derived Amides in Liquid Carbon Dioxide. Issue 31 (11th July 2013) - Kuchurov, Ilya V.; Fomenkov, Igor V.; Zlotin, Sergei G.; Tartakovsky, Vladimir A.
Abstract N‐Nitro‐ and N, N‐dinitroamides of carbonic, sulfuric and oxalic acids are prepared by nitration of the corresponding amides with dinitrogen pentoxide in liquid carbon dioxide.